Time trends and regional variations in prices of anticancer medicines in China - Zhang, Jinwei; Hu, Shuchen; Liu, Xingyu; Liu, Xiaoyong; Zhang, Jieqiong; Yang, Caijun; Fang, Yu (Frontiers in Pharmacology, 2024)
Introduction: High prices, as a main factor, contributed to the lack of adequate access to essential anticancer medicines, especially for patients in developing countries. The Chinese Government has introduced a series of policies to control the prices of medicines during the last decade, but the effect on anticancer medicine is not yet clear. Methods: To evaluate the time trends and regional variation in the price of essential anticancer medicines in China, we used the procurement data of anticancer medicines from 2015 to 2022. We selected 29 anticancer medicines from the 2018 Chinese National Essential Medicines List. To measure the cost of a medicine, we used defined daily dose cost -the cost per defined daily doses. At national level, we focused on the price changes over time and compared the price between medicine categories. At provincial level, we assessed price variation among provinces over time. Results: For prices at the national level, all 6 targeted medicines exhibited a continuous decrease trend in price. Out of 23 non-targeted medicines, 4 (17·39%) experienced continuous increases in prices, and 9 (39·13%) showed price decreases from 2015 to 2019 and then an upward trend during 2019-2022; Of the remaining non-targeted medicines, 7 (30·43%) had continuous price decreases and 3 (13.04%) had price increases followed by decreases. For prices at the provincial level, provincial price variation became smaller for almost all targeted medicines, except rituximab; for 11 out of 23 non-targeted medicines, provincial price variations became larger. During the study period, the proportion of price-increased medicines in each province was geographically correlated, and no significant relationship between prices and GDP per capita was observed for both targeted and non-targeted anticancer medicines. Conclusion: The prices and regional disparity of most targeted anticancer medicines were decreasing, while for nearly half of the non-targeted anticancer medicines, the prices were increasing and the regional disparity became wider, which may lead to compromised access to these essential anticancer medicines and raise inequity health outcome among regions.